Investigating the protective effects of aged garlic extract on cyclosporin-induced nephrotoxicity in rats. - Wongmekiat O. (2014)
Cyclosporin A (CsA) nephrotoxicity has been described in solid organ recipients and in the patients who were treated for autoimmune diseases. Reactive oxygen species-induced oxidative stress and lipid peroxidations are implicated in the pathophysiology of CsA-induced renal injury. Aged garlic extract (AGE) has been reported to exhibit potent antioxidative and free radical scavenging abilities in various disease conditions. The present study was designed to investigate whether AGE could possibly have a protective effect against nephrotoxicity induced by CsA. Male Wistar rats were treated orally with CsA (50 mg/kg/day), CsA + AGE (0.25, 0.5, 1, and 2 g/kg/day started 3 days before the first dose of CsA), or the vehicle of CsA for a period of 10 days. Blood urea nitrogen, serum creatinine, creatinine clearance, and renal histopathological changes were evaluated after 24 h of the last treatment. CsA caused an increase in blood urea nitrogen and serum creatinine by 117 and 100%, respectively, whereas it decreased creatinine clearance by 78% compared with the vehicle-treated rats (all P < 0.001). AGE treatment (0.5, 1 and 2 g/kg) significantly protected animals against CsA-induced biochemical changes, albeit blood urea nitrogen and creatinine clearance in the 0.5 g/kg AGE treated-animals were only partially restored. Kidney sections taken from CsA-treated rats showed severe vacuolations and tubular necrosis. These histopathological changes were markedly improved by pretreatment of rats with AGE at the dose of 0.5--2 g/kg. The results indicate that AGE ameliorates renal dysfunction and morphological changes induced by CsA, and imply that it could be a beneficial remedy for attenuating the CsA nephrotoxicity.